Linkage of Entrepreneurial Orientation on Business Performance of Women Entrepreneurs and Mediation Role of Competitive Advantage - Fivi Anggraini; Daniati Puttri; Hana Nabila (Jurnal Manajemen dan Kewirausahaan, 2022)
Entrepreneurial orientation is an important mechanism for small and medium enterprises to persist in a dynamic business atmosphere. This study intends to inspect the role of competitive advantage in the connection between entrepreneurial orientation and business performance Small and medium business women entrepreneurs where the population of this study. They were engaged in culinary businesses registered with the Department of Cooperatives SMEs, Padang City, West Sumatra. The random sampling method in a survey method is used in data collection. The Slovin formula with the calculation results of 97 culinary SMEs. This study used the SmartPLS (Partial Least Square) program in analyzing the data and test hypotheses. The results of hypothesis testing showed that competitive advantage significantly affects the connection between entrepreneurial orientation and women's business performance. This study suggests that the women entrepreneurs with entrepreneurial orientation attitudes are to create added value and competitive advantage for the businesses. Hence, their businesses have more advantages than the other similar businesses, which do not have an entrepreneurial orientation attitude.